Efektifitas Wound Cleansing Daun Bidara Arab (Ziziphus Spina- Christi L.) Terhadap Penyembuhan Diabetic Foot Ulcer - Vita Sabela; Imroatul Farida; Christina Yuliastuti (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2022)
Type 2 DM is a metabolic disorder disease characterized by an increase in blood sugar due to insulin resistance and can cause Diabetic Foot Ulcer (DFU) which can be cured by wound cleansing. The study used a Pre-Post control group design with a measurement time of 16 days involving 40 patients who were divided into 2 groups and selected randomly. The method of analysis used the Wilcoxon and Mann-Whitney. The instrument uses standard operating procedures for wound cleansers made from the decoction of Arabic bidara leaves and the Bates-Jensen Wound Assessment Tool (BWAT). Data analyzed using Mann-WhitneyÂ  (p= 0.586) showed that there was no difference in the mean after wound cleansing in the intervention group and after wound cleansing in the control group, but there was a difference in the decrease in indicators. Â The intervention group reduced 8 BWAT indicators consisting of wound edges, Necrotic Tissue Type, Necrotic Tissue Amount, exudate type, Exudate Amount, Skin Color Surrounding the Wound, Peripheral Tissue Edema & Induration. while the control group decreased 6 BWAT indicators consisting of Necrotic Tissue Type, Necrotic Tissue Amount, Exudate Amount, Skin Color Surrounding the Wound, Peripheral Tissue Edema & Induration. Arabic bidara leaves contain flavonoids as anti-inflammatory and antioxidants as well as alkaloids, tannins, and Christine as antibacterial. This research can be used as an evidence-based practice for DFU wound care.